Management features of elderly and senile patients with non-ST elevation acute coronary syndrome in clinical practice - E. V. Konstantinova; S. O. Denisova; A. D. Shcherbatsevich; M. I. Kalinina; A. O. Chernikov; N. A. Rahimi; A. A. Velikotsky; E. V. Ploshchenkov (Кардиоваскулярная терапия и профилактика)
Aim. Comparative analysis of two groups of patients with non-ST elevation acute coronary syndrome (NSTE-ACS) in age subgroups 60-74 years (elderly patients) and 75 years and older (senile patients); comparison of the coronary angiography (CAG) performance rate with percutaneous coronary intervention (PCI) consideration and time to intervention; evaluation of comorbidities associated with PCI non-performance in clinical practice in the selected subgroups of patients.Material and methods. The study included 580 patients aged 60 years and older (60-74 years (elderly patient group) and 75 years and older (senile patient group)), hospitalized at the regional vascular center of City Clinical Hospital in Moscow during the period from January 01, 2021 to December 31, 2022 with the diagnosis of NSTE-ACS. The decision to perform CAG with possible PCI was made by hospital physicians in the routine order of daily clinical practice. Statistical analysis was performed in Microsoft Excel 19.Results. In the group of senile patients, there was a comparatively higher percentage of women, patients with a final diagnosis of myocardial infarction, prevalence of anemia, chronic and Killip class ≥II acute heart failure, atrial fibrillation, and stage ≥3 chronic kidney disease. CAG/PCI was performed in the elderly patient group in 91,5% of cases, which was more frequent compared to the senile patient group, where the intervention was performed in 85% of cases (p=0,015). Mostly, CAG/PCI in both groups was performed within the first day of hospital admission. Anemia was significantly more common in patients aged 60-74 years in the conservative strategy groups, and aortic stenosis was more common in those aged 75 years and older. In any age group with non-performance of CAG/PCI, a significant frequency of in-hospital mortality was observed.Conclusion. Patients with NSTE-ACS of elderly and senile age included in the study predominantly underwent invasive treatment within the first day of hospitalization. The elderly and senile age patient groups differed in the prevalence of revascularization, comorbidities and in-hospital outcomes, and did not differ in the time and treatment strategy. The subgroups with interventional treatment more often had a favorable in-hospital outcome.